2010
DOI: 10.3844/ajbbsp.2010.136.140
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Adiponectin Receptors in Human Placenta and Its Possible Implication in Gestational Diabetes

Abstract: Problem statement: Similar to obese patients and type 2 diabetic patients, adiponectin levels are reduced in former Gestational Diabetes Mellitus (GDM) patients and are lower in GDM women during late pregnancy compared with pregnant control subjects matched for BMI. Diabetic insult at later stages in gestation, such as may occur in gestational diabetes, will foremost lead to shortterm changes in a variety of molecules for key functions including gene expression in the placenta. Approach: In this study we asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…Further experiments are in progress in our laboratory. Lastly, we showed that in human placenta, ADIPOR2 is 10- to 100-fold less expressed than ADIPOR1 , as generally described in other tissues and cell types [52, 53]. Interestingly, we observed that maternal obesity is associated with a significantly lower ADIPOR1 m RNA expression on the maternal side of the placenta and a significantly lower ADIPOR1 protein expression in the whole placental tissue.…”
Section: Discussionsupporting
confidence: 78%
“…Further experiments are in progress in our laboratory. Lastly, we showed that in human placenta, ADIPOR2 is 10- to 100-fold less expressed than ADIPOR1 , as generally described in other tissues and cell types [52, 53]. Interestingly, we observed that maternal obesity is associated with a significantly lower ADIPOR1 m RNA expression on the maternal side of the placenta and a significantly lower ADIPOR1 protein expression in the whole placental tissue.…”
Section: Discussionsupporting
confidence: 78%
“…Because the samples of control group and also samples of treated group are used as calibrators, the expression levels are set to 1. Because the relative quantities of the OPG&RANKL gene are normalized against the relative quantities of the endogenous control B-actin gene fold expression changes are calculated using the equation 2 -ΔΔct in the study of Alhusseini et al (2010).…”
Section: Real-time Pcr Analyses For Mrna Expression Of Bone Opg and Rmentioning
confidence: 99%
“…However, more sensitive techniques have determined that the placenta does not produce endogenous adiponectin [ 119 , 170 , 171 ]. Adiponectin in the maternal circulation does not cross the placenta; however, adiponectin receptors (ADIPOR1 and ADIPOR2) are present in the placenta [ 163 , 165 , 172 ]. Placental signalling by adiponectin receptors impacts nutrient transport and fetal growth [ 34 , 173 ].…”
Section: Adiponectinmentioning
confidence: 99%